#TITLE_ALTERNATIVE# - Wibisono Budhi (NIM 23095028), Yogi
ABSTRACT: One of the most design trends and requirements in synthesis gas plant is process and heat integration via additional pre-reformer or post-reformer on existing plant. This research is conducted on the study of adiabatic and non-adiabatic pre-reformer application in an ammonia plant PUSRI I-B. The engineering advantages are the fuel consumption reduction, no carbon formation, increase thermal efficiency, decrease flue gas emission like NOx and CO2. Pre-reformer is a catalytic reactor placed in the up stream of primary reformer to carry out the endothermic steam gas reforming of natural gas. At temperature less of 500 degree C, the cracking reaction plays the main role of the process, meanwhile the natural gas steam reforming has not carried out thermodynamically. The objectives of this research are to consider the performance of conventional reformer and modified reformer via additional pre-reformer. Modeling and simulation are to determine the mass and energy allocation thermodynamically. The study on chemical reactor engineering is accomplished to investigate the effects of additional pre-reformer on the performance of primary reformer. The simulation results show that the additional pre-reformer on existing plant by the use of heat sensible of secondary reformer effluent may reduce the fuel consumption (6-27%), decrease CH4 conversion in primary reformer (10-29%), and decrease steam production in waste heat boiler (15-29%). The heavy hydrocarbons are not detectable in the process gas fed into primary reformer, so ensure no carbon formation in primary reformer and give opportunity to decrease steam to carbon ratio. The performance test by increasing the capacity up to 50% on modified models did not show the change of reactor performance, so there is an opportunity to increase the capacity of synthesis gas production. Finally, the study on steam balance, momentum balance, temperature profile of actual process gas and plant layout are strongly required.